Description and genetic variation of a distinct species of Potyvirus infecting saffron (Crocus sativus L.) plants in major production regions in Iran. (10th October 2018) - Parizad, Shirin; Dizadji, Akbar; Koohi Habibi, Mina; Winter, Stephan; Kalantari, Siamak; Movi, Shahrbanoo; García‐Arenal, Fernando; Ayllón, Maria A.
Abstract : Saffron ( Crocus sativus L.), a highly valuable crop famous for the unique taste, aroma, colour and medicinal properties of the stigmas, is widely cultivated in Iran. During 2011–2016, a total of 965 samples were randomly collected from six important saffron growing provinces of Iran to test for the presence of viruses. Assays revealed the presence of a distinct species of the genus Potyvirus, which has been tentatively named saffron latent virus (SaLV). Phylogenetic analysis of the SaLV complete genome sequence, 9, 693 nucleotides (nt) excluding poly(A) tail, revealed that this virus grouped into Bean common mosaic virus subgroup in the genus Potyvirus with the closest relative being Bean common mosaic necrosis virus . A number of distinct plant species were evaluated for the host range of SaLV; Chenopodium amaranticolor and Chenopodium quinoa were found to be systemic hosts of SaLV. There were no nucleotide sites that indicated any recombination events, and the analysis of the coat protein (CP) sequence of 50 samples, collected from different geographical origins, did not show spatially structured diversity. Overall, our data shows strong negative selection pressure in CP, estimated by nucleotide sequences. The relevance of SaLV for saffron production in Iran remains to be established. Abstract : During 2011–2016, a total of 965 saffron ( Crocus sativus L.) samples were randomly collected from Iran, assays revealed the presence of a distinct species of the genus Potyvirus, tentatively named saffron latent virus (SaLV). SaLV grouped into Bean common mosaic virus subgroup in the genus Potyvirus ‐based on phylogenetic analysis of the complete genome sequence (9, 693 nucleotides excluding poly(A) tail). Chenopodium amaranticolor and Chenopodium quinoa were found to be systemic hosts of SaLV. No recombination events have been identified in the genome of SaLV. Our data shows strong negative selection pressure in coat protein, estimated by nucleotide sequences.